Spiritual Motivation In The Qur'an Within The Framework Of Contemporary Da’wah - Hasna Azhaari; Hamidullah Mahmud Hamidullah Mahmud (UIN Kiai Haji Achmad Siddiq Jember, 2026)
Preparing oneself to face the developments of the times, technology, and various understandings, the presence of modern society requires a foundation that always accompanies the practice of Islamic values, namely the Qur'an, which contains a source of inspiration and motivation for Muslims, especially for a preacher in delivering his message. The purpose of this research is to build the resilience and authority of preachers in facing contemporary social issues in the wise dissemination of Islamic preaching without coercion and making the Qur'an a source of motivation. This research method is descriptive qualitative through a literature study approach. The data sources used are revelatory text studies, analysis of books and articles related to the motivational perspective of the Qur'an and its relevance to contemporary da'wah. The results of this study show the implementation of contemporary da'wah carried out by da'i to achieve the application of self-transcendence by mad'u can be proven by actual practice through da'i who pay attention to the principles of persuasive approaches as guidelines and understand the Qur'an as a source of motivation, by paying attention to honesty and openness, using logical arguments, paying attention to the use of narratives and stories, and finally delivering da'wah that touches the emotions. For a da'i very important to convey his message in accordance with the problems of modern society, namely through contemporary da'wah that pays attention to a persuasive approach in accordance with the teachings of the Qur'an as a source of motivation.